Crianças com Transtorno de Déficit de Atenção e Hiperatividade (TDAH): os sentidos produzidos sobre a infância na perspectiva de familiares e profissionais da educação educadores - Batista, Karina de Andrade (2019)
Understanding the meanings attributed to childhood from the diagnosis of Attention Deficit Hyperactivity Disorder (ADHD) is to recognize that we are facing a plural and multifaceted childhood. These are, therefore, childhoods, where each represents a complex construct, constituted by the interaction of social, cultural, biophysiological and emotional factors, under the direct influence of the historical and political conjuncture. In this context, the look and meaning that social subjects operate on children play a fundamental role in their constitutive process. Based on this understanding, the main objective of the research was to understand the meanings produced about childhood from the perspective of family members and educators of children diagnosed with ADHD. Aware that in our culture one of the main social roles required for childhood is the development of school learning, this study was carried out in the Education network of the city of Fortaleza-CE, with the setting of two Municipal Elementary Schools (EMEF I and EMEF II). In our society, the school appears as a socially established space for childhood, actively contributing to the pedagogical and formative process of its subjectivity. The occurrence of events that are outside the norm is constantly experienced with anguish and considered as a dysfunction of the organism, therefore, it should be treated in the field of health. It is in this relationship between educational processes and mental health that the diagnosis of ADHD is inserted. In this perspective, to conduct this research, initially, a Field Diary was produced to systematize the observations and experiences of the scenario under study. The notes, descriptions of the processes, as well as speeches, behaviors and personal impressions, made up this first moment. Subsequently, semi-structured interviews were conducted with parents and educators and an analysis of discursive practices was performed. This study, part of the understanding that the verbal meanings and representations contained in the speeches are the result of several domains of knowledge and influence ways of thinking and understanding childhood and ADHD, in addition to providing evidence of a way of being and constituting a childhood specific. As a result, this analysis pointed out that the process of individualizing the causes of non-learning is growing, corroborating with an individualizing and pathological perspective, understood from a biomedical perspective. This situation, while raising issues related to the structuring and functioning of health and education networks, places us in front of a scientific ideological process in which the field of biomedical knowledge still prevails in care processes. It is necessary to recognize the subject in its entirety, considering the biopsychosocial factors. To reduce the analysis of the subject to a single category would be to reduce his possibilities of existence. Likewise, the Education and Health Networks need to be thought out in a broader way, in addition to existing barriers between the fields of knowledge. Discussing the possibility of an interprofessional approach in the construction of interred work is a challenging perspective, but enhancing an expanded care that tends to break with the biologizing paradigm still in force today.